Implementasi Teknologi Dehydrated Honey Dalam Meningkatkan Kualitas Produk Madu dan Jamu - Mas, Ahmad Baihaqi; Muhammad, Alief; Nafis, Raihan; Abdillah, Hartawan; Asrori, Tamam; MutindaTeguh Widayanto (Fakultas Teknik, Universitas PGRI Banyuwangi, 2025)
This community service program aims to improve the quality of honey products produced by small-scale producers in Probolinggo by implementing the Dehydrated Honey Machine. The main problem faced by partners is the high moisture content in honey (28%), which exceeds the Indonesian National Standard (SNI 8664:2018) limit of less than 22%. High moisture content reduces shelf life, product quality, and market acceptance, especially in pharmacies and online stores. The program was conducted through participatory methods consisting of socialization, training, technology implementation, and monitoring-evaluation. The Dehydrated Honey Machine with a capacity of 15 liters per 3 hours was installed at the partner’s production site, followed by training on operation and maintenance. After implementation, the moisture content of honey decreased to 17–18%, in line with the standard requirements. This improvement has extended the shelf life of honey, increased the selling price, and reduced product rejection. The program demonstrates that appropriate technology transfer effectively enhances production quality and competitiveness of local honey producers.